2007
DOI: 10.1007/s10562-007-9222-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Ethanol Steam Reforming Over Ni/CeO2 Nanocomposite Catalysts

Abstract: The organic polymer chitosan was used as the polymeric precursor for the synthesis of Ni/CeO 2 nanocomposite catalysts. The materials were characterized by N 2 physisorption, H 2 chemisorption, AA, XRD, TGA, TPR, SEM and TEM analyses. The catalysts provide very good reactivity in ethanol steam reforming compared to the conventional Ni/CeO 2 catalyst prepared by the impregnation method using a commercial support. High hydrogen selectivity (>75%) was obtained on Ni/CeO 2 catalysts by operating at a temperature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…To date, most studies have focused on developing catalysts with high activity and stability for ethanol steam reforming. Although the active phase, such as cobalt [1,2], copper [3,4], as well as noble metals present very interesting behavior in ethanol steam reforming [5][6][7], Ni catalyst is the most favorable candidate due to low cost and high activity [8][9][10][11][12]. However, Ni catalyst easily suffers severe deactivation caused by sintering and coke deposition with time on stream.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies have focused on developing catalysts with high activity and stability for ethanol steam reforming. Although the active phase, such as cobalt [1,2], copper [3,4], as well as noble metals present very interesting behavior in ethanol steam reforming [5][6][7], Ni catalyst is the most favorable candidate due to low cost and high activity [8][9][10][11][12]. However, Ni catalyst easily suffers severe deactivation caused by sintering and coke deposition with time on stream.…”
Section: Introductionmentioning
confidence: 99%
“…1023 K. The activity of the catalyst was attributed to its ability to scavenge coke deposition on the Ni surface by lanthanum oxycarbonate species which exists on top of the Ni particles under reaction conditions. But the catalyst did not exhibit good stability [30].…”
Section: Catalytic Investigationsmentioning
confidence: 97%
“…A high oxygen mobility (redox property), high oxygen storage capacity, strong interaction with the supported metal (strong metal-support interaction) and their ease of modification promoted several investigations of hydrogen production by SRE over CeO 2 supported catalysts [27][28][29]. Fajardo et al [30] performed SRE with S/EtOH of 3 at 673 K over Ni supported over CeO 2 catalyst prepared by using a biopolymer polymerization method. They showed that formation of ethylene due to dehydration reaction was absent over this catalyst, unlike that prepared by conventional impregnation of commercial CeO 2 .…”
Section: Catalytic Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous publications [10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27]32] have studied the catalytic behavior for ESR of Ni over different supports, including CeO 2 . In order to compare the performance of our Ru based catalyst with a more studied catalyst, NiPI catalyst was synthesized with the same method and it was tested for ESR under the same experimental conditions.…”
Section: Insights In the Rupi Catalyst Performance: Comparison With Nipimentioning
confidence: 99%